Jobs in EU micro firms (Luxembourg, 2001)
"A quarter of the European workforce are currently employed in microfirms - firms with less than 10 employees. A recent foundation project summary confirms what they may have already suspected: their general job quality is no match for those of counterparts in the rest of the working population. The leaflet summarises the most relevant findings to emerge from research and debate activities promoted by the Foundation on employment and the quality of work in small and medium-sized enterprises (SMEs), with a particular focus on micro firms."